2017
DOI: 10.1007/s00421-017-3569-1
|View full text |Cite
|
Sign up to set email alerts
|

β-alanine supplementation improves in-vivo fresh and fatigued skeletal muscle relaxation speed

Abstract: PurposeIn fresh muscle, supplementation with the rate-limiting precursor of carnosine, β-alanine (BA), results in a decline in muscle half-relaxation time (HRT) potentially via alterations to calcium (Ca2+) handling. Accumulation of hydrogen cation (H+) has been shown to impact Ca2+ signalling during muscular contraction, carnosine has the potential to serve as a cytoplasmic regulator of Ca2+ and H+ coupling, since it binds to both ions. The present study examined the effect of BA supplementation on intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
2
13
3
Order By: Relevance
“…Ahlborg et al (1972) predicted the time to exhaustion at 45% of maximal voluntary contraction to be about 80 s, whereas the hold-time of participants in Derave et al (2007) study lasted longer than 175 s. Exercise of longer duration utilizes the oxidative system for metabolic energy production to a greater extent than shorter-duration exercise, leading to lower H + accumulation. Furthermore, our results contradict with those of Kendrick et al (2008) who reported no improvement in quadriceps isokinetic force after β-alanine supplementation (6.4 g day −1 for 10 weeks), and Hannah et al (2015) and Jones et al (2017), who reported no change in quadriceps maximal voluntary isometric force production or the force-frequency relationship after β-alanine supplementation (6.4 g day −1 for 28 days). The differences in findings may be related to the exercises utilized, as the isometric protocols by Kendrick et al (2008), Derave et al (2007), Hannah et al (2015) and Jones et al (2017) may not have elicited the extent of fatigue to maximize the benefits achieved from a greater buffering capacity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Ahlborg et al (1972) predicted the time to exhaustion at 45% of maximal voluntary contraction to be about 80 s, whereas the hold-time of participants in Derave et al (2007) study lasted longer than 175 s. Exercise of longer duration utilizes the oxidative system for metabolic energy production to a greater extent than shorter-duration exercise, leading to lower H + accumulation. Furthermore, our results contradict with those of Kendrick et al (2008) who reported no improvement in quadriceps isokinetic force after β-alanine supplementation (6.4 g day −1 for 10 weeks), and Hannah et al (2015) and Jones et al (2017), who reported no change in quadriceps maximal voluntary isometric force production or the force-frequency relationship after β-alanine supplementation (6.4 g day −1 for 28 days). The differences in findings may be related to the exercises utilized, as the isometric protocols by Kendrick et al (2008), Derave et al (2007), Hannah et al (2015) and Jones et al (2017) may not have elicited the extent of fatigue to maximize the benefits achieved from a greater buffering capacity.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, our results contradict with those of Kendrick et al (2008) who reported no improvement in quadriceps isokinetic force after β-alanine supplementation (6.4 g day −1 for 10 weeks), and Hannah et al (2015) and Jones et al (2017), who reported no change in quadriceps maximal voluntary isometric force production or the force-frequency relationship after β-alanine supplementation (6.4 g day −1 for 28 days). The differences in findings may be related to the exercises utilized, as the isometric protocols by Kendrick et al (2008), Derave et al (2007), Hannah et al (2015) and Jones et al (2017) may not have elicited the extent of fatigue to maximize the benefits achieved from a greater buffering capacity. Carnosine is known to enhance intracellular buffering of H + (Abe 2000), improving performance particularly during high-intensity anaerobic exercise, and β-alanine supplementation does not appear to have an effect on maximal strength production (Hoffman et al 2008;Kendrick et al 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Exercises requiring maximal strength and power or muscular endurance likely do not stress the anaerobic system enough to elicit a significant elevation in H + concentrations. Furthermore, most studies have reported no significant increases in maximal strength and power or muscular endurance (lasting less than 60 sec in duration) after BA supplementation (Hannah et al 1985;Hoffman et al 2008b;Kendrick et al 2008;Jones et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several original and review articles have described the positive effects of long-term beta-alanine supplementation on muscle performance [92][93][94][95][96], and chronic beta-alanine supplementation is a popular ergogenic strategy. It should be noted that a substantial decrease in the HIS content (~30%) in muscles and plasma after beta-alanine supplementation has been reported [89].…”
Section: Effects On Muscle Performance and Fatiguementioning
confidence: 99%